Avaliação clínica e neurofisiológica do sistema nervoso periférico na doença de Machado-Joseph - Bezerra, Marcio Luiz Escorcio [UNIFESP] (2014)
Machado Joseph disease (MJD) or spinocerebellar ataxia (SCA) type 3 (SCA3) is the most common autosomal SCA worldwide. It is characterized by progressive cerebellar ataxia, pyramidal signs, progressive external ophthalmoplegia and variable degrees of extrapyramidal involvement. Neuropathy is a well-recognized feature in MJD, but the pattern of nerve involvement is still a matter of debate. Objective: study the peripheral nerve involvement in MJD patients. Clinical and neurophysiological evaluation was performed with the objective of characterizing the pattern of nerve involvement in these individuals. Aiming to distinguish mainly among neuronopathy and distal axonopathy. Methods: in this study, 26 patients with MJD, with molecular diagnosis, were evaluated clinically and through neurophysiological methods. The clinical and neurophysiological data were compared and correlated. The pattern of nerve involvement was defined based on the abnormalities found on the neurophysiological study. Then this information was correlated with the clinical data. Results: the neurophysiological evaluation showed neuropathy n 42,5% of the patients. Among those, 81,85 showed neurophysiological signs suggesting neuronopathy. Conclusion: in the MJD sample analyzed, neuronopathy was the most common type of peripheral nerve involvement.